2015
DOI: 10.1353/aq.2015.0057
|View full text |Cite
|
Sign up to set email alerts
|

Embodied Cosmogony: Genealogy and the Racial Production of the State in Victoria Nalani Kneubuhl’s “Ho‘oulu Lāhui”

Abstract: This essay interrogates multiple representations of lāhui to index the shifting relationships between the individual and the nation in nineteenth- and twentieth-century Hawai’i, as prescribed by both Kanaka Maoli (Native Hawaiian) epistemology and US political frameworks, to suggest how a return to indigenous conceptions of the Kanaka Maoli body may liberate notions of identity and belonging from the American imposition of blood quantum. Kanaka Maoli knowledge systems elucidate the sacredness of the human body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In the study of Méndez(2021), a similar resistance movement occurred in Tarapacá, Chile, when technological modernization threatened indigenous ownership of water. The study confirms that genealogical tracing, from the 19th to 20th centuries, found that residents grew up with their knowledge of the water, something scientists would refute by offering a modern discourse on water ownership.The genealogical approach is also taken by the native Hawaiian when defining their original identity by tracing the kinship system when dealing face-to-face with the new identity of American political and cultural imperialism(Warren 2015) In addition, in an urban study in Hargeisha, Somalia, a genealogical perspective is deployed to discover how the kinship system influences governmental negotiations(Tahir 2021).The discipline over a body is also a focal study of genealogy Foucault (2019). traces the issue discussed in the genealogy discourse.…”
mentioning
confidence: 99%
“…In the study of Méndez(2021), a similar resistance movement occurred in Tarapacá, Chile, when technological modernization threatened indigenous ownership of water. The study confirms that genealogical tracing, from the 19th to 20th centuries, found that residents grew up with their knowledge of the water, something scientists would refute by offering a modern discourse on water ownership.The genealogical approach is also taken by the native Hawaiian when defining their original identity by tracing the kinship system when dealing face-to-face with the new identity of American political and cultural imperialism(Warren 2015) In addition, in an urban study in Hargeisha, Somalia, a genealogical perspective is deployed to discover how the kinship system influences governmental negotiations(Tahir 2021).The discipline over a body is also a focal study of genealogy Foucault (2019). traces the issue discussed in the genealogy discourse.…”
mentioning
confidence: 99%